Thermoelectric Modulation of Neat Ti3C2Tx MXenes by Finely Regulating the Stacking of Nanosheets - Junhui Tang; Renyang Zhu; Ya-Hsin Pai; Yan Zhao; Chen Xu; Ziqi Liang (Nano-Micro Letters, 2024)
Highlights Investigation of dispersing solvents on processing Ti3C2Tx thin films revealed that deionized water is superior to realize tight stacking and high orientation of MXene nanosheets. A simultaneous elevation of Seebeck coefficient and electrical conductivity of neat Ti3C2Tx films is achieved by increasing the centrifugal speed of MXene aqueous suspensions due to the energy filtering effect. Further construction of Ti3C2Tx nanocomposites significantly strengthens Seebeck coefficient yet disrupts the stacking of MXene nanosheets.